Agrarian Transitions in Aquarian Contexts: Fisheries Transitions in Vietnam’s Tam Giang Lagoon - Wilkings, Ann Michelle (Université d'Ottawa / University of Ottawa, 2013)
This thesis investigates agrarian transitions within aquarian contexts by investigating livelihood transitions in a small rural fishing village in central Vietnam. Examined are powers at play that inform livelihood transitions as fishers and fish farmers respond by moving in and out of different production systems in order to maintain their fishing and fish farming livelihoods. This research reveals that aquarian transitions in Vietnam could follow a similar trajectory of agrarian transitions whereby smaller, less efficient production systems make room for more efficient economies of scale. In conducting a thorough and detailed empirical analysis of production systems, the socio-economic relations that shape production systems, and natural resource governance within the Vietnamese context, this research contributes to a better understanding of the knowledge surrounding fishery resources and livelihood options.
Keywords: Vietnam; Fisheries; Livelihoods